2019
DOI: 10.3390/nano9060873
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity Assessment of Fe3O4 Magnetic Nanoparticle Exposure in Adult Zebrafish at an Environmental Pertinent Concentration by Behavioral and Biochemical Testing

Abstract: Magnetic Nanoparticles (MNPs) are widely being investigated as novel promising multifunctional agents, specifically in the fields of development for theranostics, electronics, waste water treatment, cosmetics, and energy storage devices. Unique, superior, and indispensable properties of magnetization, heat transfer, and melting temperature make MNPs emerge in the field of therapeutics in future healthcare industries. However, MNPs ecotoxicity as well as behavioral toxicity is still unexplored. Ecotoxicity anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 80 publications
(110 reference statements)
0
16
1
1
Order By: Relevance
“…Similarly, for in vitro cytotoxicity analysis when a lactate dehydrogenase (LDH) assay was performed in a BeWo b30 placental barrier model, all concentrations of uncoated Fe 3 O 4 released LDH except 3 µg/cm 2 after 24 h exposure and LDH levels were elevated from cells treated with uncoated Fe 3 O 4 at 75 and 15 ug/cm 2 representing a significant time-dependent increase of toxicity at high concentrations of 15 and 75 µg/cm 2 for uncoated Fe 3 O 4 , but not for OC-Fe 3 O 4 MNPs [ 82 ]. In a zebrafish system, Malhotra and colleagues also found that carbon-coated Fe 3 O 4 MNPs displayed superior biosafety compared to uncoated ones based on neurobehavioral and biochemical assays [ 80 ]. All these phenomena indicate that a lot of factors are involved in understanding the toxicity on a cellular and organism basis depending on dosage, concentration, time, surface chemistry, cell type, interaction medium, internalization mode, which need very elaborate studies to understand the fundamental mechanism properly in accordance to be able to use the MNPs in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for in vitro cytotoxicity analysis when a lactate dehydrogenase (LDH) assay was performed in a BeWo b30 placental barrier model, all concentrations of uncoated Fe 3 O 4 released LDH except 3 µg/cm 2 after 24 h exposure and LDH levels were elevated from cells treated with uncoated Fe 3 O 4 at 75 and 15 ug/cm 2 representing a significant time-dependent increase of toxicity at high concentrations of 15 and 75 µg/cm 2 for uncoated Fe 3 O 4 , but not for OC-Fe 3 O 4 MNPs [ 82 ]. In a zebrafish system, Malhotra and colleagues also found that carbon-coated Fe 3 O 4 MNPs displayed superior biosafety compared to uncoated ones based on neurobehavioral and biochemical assays [ 80 ]. All these phenomena indicate that a lot of factors are involved in understanding the toxicity on a cellular and organism basis depending on dosage, concentration, time, surface chemistry, cell type, interaction medium, internalization mode, which need very elaborate studies to understand the fundamental mechanism properly in accordance to be able to use the MNPs in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Malhotra and colleagues discovered that bare Fe 3 O 4 MNPs (15 nm) exposure can trigger behavioral and biochemical alterations in zebrafish. They incubated adult zebrafish with either low dose (1 ppm) or high dose (10 ppm) bare Fe 3 O 4 MNPs for 14 days and discovered no significant abnormalities at behavioral and biochemical levels in the low concentration group, whereas, significant changes in aggressiveness, speed, and locomotion behavior coupled with substantial changes in neurotransmitters and stress hormones were induced in the brains when zebrafish were challenged with high dose of Fe 3 O 4 MNPs [ 80 ]. Next, Malhotra and colleagues further tested the idea whether the toxicity of bare Fe 3 O 4 MNPs can be reduced if their surface was coated with inert substances like carbon.…”
Section: Mnp Toxicity In Vitro and In Vivomentioning
confidence: 99%
“…Recent interest has focussed on using the circadian rhythm of zebrafish locomotor activity as a metric for toxicity assessment (Li et al, 2017;Pan et al, 2017;Yang et al, 2018;Sarasamma et al, 2018aSarasamma et al, ,b, 2019Audira et al, 2019;Malhotra et al, 2019;Aluru et al, 2020;Zhao et al, 2020). The available data are summarized in Table 2.…”
Section: Biological Reviewsmentioning
confidence: 99%
“…The potential of toxicity of iron oxide NPs greatly depends on the different combinations and functionalization used. In vivo and in vitro studies on the safety of uncoated iron oxide NPs displayed cytotoxicity in erythrocytes [713] and neurobehavioral toxicity at 10 ppm [714]. However, another study did not indicate any inherent toxicity for uncoated iron oxide NPs [702].…”
Section: Iron Oxide Npsmentioning
confidence: 97%